History of the first organ transplant: blood transfusions - Karaboue, Karidia (Medicina Historica, 2023)
The term transplantation refers to various situations which differ in the type of biological material involved, how it is performed and the type of donor. We usually refer to the experience of transplantation in terms of a gift that one person donates to another: the risk, however, is that this concept is used automatically, uncritically, without any prior reflection on its characteristics. The origins and development of the first type of transplantation are found in blood transfusions, and there were numerous scientific discoveries and technical innovations at the turn of the 19th and 20th centuries which enabled transfusions to become an established practice. The common thread running through this analysis is the figure of the blood donor, initially flanked by that of the paid donor, and only since 1990 recognised as the sole legitimate source of blood and its components.